THE CHARACTERISTIC OF CYTOLOGICAL AND PCR TESTS RESULT OF FINE NEEDLE ASPIRATION (FNA) SPECIMEN FROM NECK LYMPH NODE/S ENLARGEMENT CLINICALLY DIAGNOSED AS TUBERCULOUS LYMPH ADENITIS - Winarti, Ni Wayan; Sriwidyani, Ni Putu (Medicina; Vol 43 No 3 (2012): September 2012, 2013)
Diagnosis of Tuberculous (TB) lymph adenitis is still problematic due to paucibacillar. Since histopathological biopsy examination is relatively expensive and needs times, FNA is being more frequently chosen. The specimen from FNA can be processed for cytological and PCR tests, but there is no data available describe the characteristic of the result of both methods. Hence, study is needed in order to improve knowledge and health services. A cross sectional study had been conducted from January 1st   until December 31st   , 2011, at Anatomical Pathology Laboratory of Medical School of Udayana University/Sanglah Hospital and Biomolecular Laboratory of Medical School of Udayana University. The subjects were all patients with clinical diagnosis TB lymph adenitis who met the eligibility criteria. During 6 months, there were 46 patients included in the study. They were 65% female and 35% male. The age was ranging from 5 years old until 83 years old and 30-39 years old age group was the highest in number (39%). Positive cytology result was found in 22 cases (48%), while PCR test revealed no positive result. There was significant diference between positive and negative cytology test in pain sensation category, conversely in onset, number of enlarged lymph node/s, localization, conglomeration and fixation categories. If every single clinical character was marked with score 1, node/s with accumulative scores 4-6 showed no different cytology result with node/s with score 1-3. This study shows that in detecting TB lymph adenitis using FNA specimen, cytology test was be#er than PCR
Keywords: TB lymph adenitis, FNA, cytology, PCR